2016
DOI: 10.1038/srep31286
|View full text |Cite
|
Sign up to set email alerts
|

MATSAP: An automated analysis of stretch-attend posture in rodent behavioral experiments

Abstract: Stretch-attend posture (SAP) occurs during risk assessment and is prevalent in common rodent behavioral tests. Measuring this behavior can enhance behavioral tests. For example, stretch-attend posture is a more sensitive measure of the effects of anxiolytics than traditional spatiotemporal indices. However, quantifying stretch-attend posture using human observers is time consuming, somewhat subjective, and prone to errors. We have developed MATLAB-based software, MATSAP, which is a quick, consistent, and open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Rodents naturally elicit this risk assessment behaviour when in a new environment by performing a forward elongation of the head followed by retraction to the initial position. However, a high frequency of this behaviour shows a high level of anxiety (Holly et al, 2016). In line with findings from this study, aluminium has been reported to induce anxiety and memory decline (Crépeaux et al, 2017;Morris et al, 2017;Olajide et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Rodents naturally elicit this risk assessment behaviour when in a new environment by performing a forward elongation of the head followed by retraction to the initial position. However, a high frequency of this behaviour shows a high level of anxiety (Holly et al, 2016). In line with findings from this study, aluminium has been reported to induce anxiety and memory decline (Crépeaux et al, 2017;Morris et al, 2017;Olajide et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, stretch attend postures occur a risk-assessment behavior indicating that the rodent is hesitant to move from its present location to a new position 52 , 53 ; thus, a high frequency of these postures indicates a higher level of anxiety. We observed that NMS rats showed decreased stretching numbers in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with their robust avoidance of the center of the OF, the number of transitions of Nlgn2 KO mice was too low to perform a powerful statistical analysis (4.4 ± 2.6 transitions). However, we noticed that Nlgn2 KO mice displayed frequent stretch-attend postures (SAPs), a risk-assessment behavior that reflects an internal conflict between anxiety and the exploratory drive 30,31 (Fig. 3j).…”
Section: Resultsmentioning
confidence: 99%